Impact of Fungal MAPK Pathway Targets on the Cell Wall - Jacky Chow; Marysa Notaro; Aditi Prabhakar; Stephen J. Free; Paul J. Cullen (Journal of Fungi, 2018)
The fungal cell wall is an extracellular organelle that provides structure and protection to cells. The cell wall also influences the interactions of cells with each other and surfaces. The cell wall can be reorganized in response to changing environmental conditions and different types of stress. Signaling pathways control the remodeling of the cell wall through target proteins that are in many cases not well defined. The Mitogen Activated Protein Kinase pathway that controls filamentous growth in yeast (fMAPK) was required for normal growth in media containing the cell wall perturbing agent Calcofluor White (CFW). A mass spectrometry (MASS-SPEC) approach and analysis of expression profiling data identified cell wall proteins and modifying enzymes whose levels were influenced by the fMAPK pathway. These include Flo11p, Flo10p, Tip1p, Pry2p and the mannosyltransferase, Och1p. Cells lacking Flo11p or Och1p were sensitive to CFW. The identification of cell wall proteins controlled by a MAPK pathway may provide insights into how signaling pathways regulate the cell wall.